From the Faith of Lamas to Global Buddhism: The Construction of Buddhist Tradition in Russian Trans-Baikal from the Eighteenth to the Early Twentieth Century - Nikolay Tsyrempilov (Käte Hamburger Kolleg Dynamics in the History of Religions between Asia and Europe, 2019)
The article invites readers to reconsider the history of Buddhism in Russian Trans-Baikal as a gradual process of negotiation and redefinition that involved different actors: lamas, Russian imperial officials of various levels, Orthodox missionaries, Buriat national activists, Saint Petersburg Orientologists, modern Buddhist reformers and conservatives. The process involved the construction of the centralized and subordinated confessional group out of scattered communities of lamas in the course of the nineteenth century, Irkutsk Orthodox Diocese’s attempts first to downgrade the faith of lamas to idol-worship and then to normalize ‘corrupted Buddhism’, and the 'discovery' of the larger Buddhist world by some Buriat lamas and their attempts to bring it back to ‘authentic forms’. The article shows what exactly had brought Russian officials and then Buriat Buddhists themselves to the idea that their religious tradition, which historically was labeled merely as Lamaistvo, is a part of the emerging conception of global Buddhism.
Keywords: Buddhism; Trans-Baikal; tradition construction; global Buddhism; type of access: open access